Legacy‐micropollutant contamination levels in major river basins based on findings from the Rhône Sediment Observatory. Issue 2 (24th February 2022) - Delile, Hugo; Dendievel, André‐Marie; Yari, Anice; Masson, Matthieu; Miège, Cécile; Mourier, Brice; Coquery, Marina
Abstract: For more than half a century, chemical contamination has progressively spread to all the large river basins. Large river outlets integrate multiple anthropogenic pressures in watersheds, making them the largest source of sediment‐bound contaminants to continental shelf areas. However, comparing particulate micropollutant contaminations between the large river basins is a challenging task, especially due to the scarcity of long‐term river monitoring programs. Here we address this issue, with a focus on legacy particulate micropollutants (polychlorobiphenyls [PCBi], polycyclic aromatic hydrocarbons [PAHs] and trace metal elements [TME]) yields. For this purpose, we employed a bottom‐up multiscale approach to chemical contamination in river basins that takes micropollutant yields measured in the Rhône River sub‐basins (France) as a benchmark of other large river basins. Data on the Rhône River basin came from a unique 10‐year‐long monitoring program within the Rhône Sediment Observatory (OSR), and were compared to data gathered on 18 major worldwide river outlets. The Rhône River basin is far cleaner now than a few decades ago, likely due to environmental regulations. At a wider spatial scale, our results depict an overall contamination gradient splitting the most heavily contaminated river basins, located in developing and industrializing low‐to‐middle‐income countries, from the least contaminated rivers located in developed high‐income countries. We argue that chemical contamination levels of large river basins depend on their stage of economic development. Abstract : For more than half a century, chemical contamination has progressively spread to all the large river basins. Comparing particulate micropollutant contaminations between the large river basins is a challenging task, as there is a lack of large‐scale monitoring for estimating chemical contamination at river outlets. Here we address this issue using yields of legacy micropollutants in a bottom‐up multiscale approach, from the well‐monitored Rhône River sub‐basins (as benchmark) up to the major large river basins. Results show an overall chemical contamination gradient that splits the most‐contaminated river basins, located in developing and industrializing low‐to‐middle‐income countries, from the least contaminated rivers located in developed high‐income countries. Data from the pluri‐decadal monitoring program on the Rhône River basin shows that since the 1980s, this river has transitioned from the more‐contaminated group to the less‐contaminated group.